PENGARUH KOMUNIKASI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN AUTO2000 MT. HARYONO BALIKPAPAN - Aprilian, Riefky; Ariani, Misna; Yuliani, Tutik (Jurnal GeoEkonomi, 2024)
This research aims to determine the influence of communication, work discipline and work environment on job satisfaction of Auto2000 MT. Haryono Balikpapan employees. The population in this study were 97 Auto2000 MT. Haryono Balikpapan employees consisting of 62 permanent employees and 35 contract employees. By using a total/census sampling technique, the sample used was 97 respondents. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to manage data. The results of this research indicate that the Communication variable influences Auto2000 MT. Haryono Balikpapan Employee Job Satisfaction. Work Discipline Variables influence Auto2000 MT. Haryono Balikpapan Employee Job Satisfaction. Work Environment Variables influence Auto2000 MT. Haryono Balikpapan Employee Job Satisfaction.